PSIKOLOGI SASTRA YANG TERDAPAT PADA CERPEN LISTRIK MATI LAGI KARYA ABDULLAH ALAWI - Saptiana Sulastri; Lusia Rani Kurnia; Margareta Paskalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the psychological aspects in the short story “Listrik Mati Lagi” by Abdullah Alawi through a literary psychology approach. The problem addressed in this research is how the psychological conditions of the characters are portrayed amid economic pressure and environmental limitations. The objective of this study is to identify and describe the inner conflicts, emotional responses, and defense mechanisms experienced by the characters. This research employs a qualitative descriptive method, with data collected through close reading and note-taking techniques on narrative elements, dialogues, and character actions. The analysis is based on psychological literary theory focusing on anxiety, inner conflict, and defense mechanisms. The results show that the characters experience various psychological pressures, including anxiety, fear, and emotional tension. The father figure tends to exhibit silence as a form of defense mechanism, while the mother expresses anxiety through complaints. Meanwhile, the child character reflects subjective perception shaped by fear and imagination, especially in dark situations caused by power outages. These findings indicate that environmental conditions, such as economic hardship and physical surroundings, significantly influence the psychological state of the characters. Therefore, the short story not only represents social reality but also reveals complex psychological dynamics within human life.